EVALUATION OF HOUSING FINANCING ASSISTANCE POLICIES FOR LOW-INCOME PEOPLE IN DKI JAKARTA - Khayrunnisa, Fauzia Maurizka; Wijaya, Chandra (Ridwan Institute, 2024)
This study aims to find out how to evaluate housing financing assistance policies for low-income people in the DKI Jakarta area. The research used a descriptive research design with a quantitative approach. The data collection technique used was a mixed method through respondent questionnaire surveys, interviews, and literature studies. The sample in this study consisted of respondents who had received the benefits of housing funding assistance policies and those who had not. The results of this study show that the leveling in the evaluation of housing finance assistance policies can be measured based on two indicators, namely, the policy has been evenly and comprehensively distributed, and the usefulness of the policy in overcoming the housing backlog in DKI Indonesia is felt by MBR. Meanwhile, from the utility aspect, the housing financing financing assistance policy is beneficial for MBR in acquiring subsidized houses. Furthermore, there are still shortcomings that must be corrected both from the supply aspect housing, strengthening policy monitoring and evaluation, strengthening governance and institutions, strengthening laws and regulations, strengthening collaboration and synergy between stakeholders, and strengthening collaboration. This study offers valuable insights for policymakers to design more equitable and sustainable housing financing strategies, addressing critical socio-economic issues in urban housing.